Surface Alloying Of Titanium With Nickel By Using Cathodic Arc Based Plasma Treatment - Nagihan Sezgin; Erkan Kaçar; Kürşat Kazmanlı; Mustafa Ürgen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, cathodic arc electron / metal iontreatment (CA-EMIT) technique was used to modify Ti surfaces in Ni cathodic arcplasma. At this novel method, AC bias was applied to the Ti substrates. Inpositive cycle of AC bias, the substrates were heated by electrons while nickelions were directed toward the substrate surface in negative cycle. The surfacemodification processes were performed at 5 different temperatures: 1073 K (800°C), 1273 K (1000 °C), 1373 K (1100 °C), 1473 K (1200 °C) and 1573 (1300 °C).The samples were characterized by XRD, SEM and EDS analysis. The effect ofsubstrate temperature and cathode current were investigated on microstructureof the samples. This process provides rapid diffusion of nickel into thetitanium and high diffusion depths were obtained compared to literaturestudies.